-79-9x=7x+17

Simple and best practice solution for -79-9x=7x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -79-9x=7x+17 equation:


Simplifying
-79 + -9x = 7x + 17

Reorder the terms:
-79 + -9x = 17 + 7x

Solving
-79 + -9x = 17 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-79 + -9x + -7x = 17 + 7x + -7x

Combine like terms: -9x + -7x = -16x
-79 + -16x = 17 + 7x + -7x

Combine like terms: 7x + -7x = 0
-79 + -16x = 17 + 0
-79 + -16x = 17

Add '79' to each side of the equation.
-79 + 79 + -16x = 17 + 79

Combine like terms: -79 + 79 = 0
0 + -16x = 17 + 79
-16x = 17 + 79

Combine like terms: 17 + 79 = 96
-16x = 96

Divide each side by '-16'.
x = -6

Simplifying
x = -6

See similar equations:

| x-1=6x | | 4q=6.8 | | 4Y=10+34 | | 5x+6=-30-7x | | y=43.81+-0.395x | | -30-3x=5-8x | | 4x-2y=-8 | | y=43.81-0.395x | | 0.3=0.01x+2.9 | | 53-5x=7x+17 | | 5x+11=91-5x | | 8n-15=65 | | y=85-13.254x | | 0.3X=0.01+2.9 | | 3x+2+x-6=25 | | -2x-127+11x=107 | | -4x-6x-93=107 | | 0.5+3=4.5 | | -10x-2x-87=57 | | 47-6x=12x+17 | | 4(x+2)=22 | | 5.5w=247.5 | | 0.03x-2.1=0.3 | | -11x-108-6x=147 | | 2x^2+50=0 | | 16t=540 | | -10x-44+5x=21 | | 5x=225 | | 12-10x=42-31x | | 2x^2-24x+8=0 | | 5x-5=5(x-7) | | -75-9x=9x+15 |

Equations solver categories